2010
DOI: 10.4269/ajtmh.2010.10-0279
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence Survey of Chikungunya Virus in Bagan Panchor, Malaysia

Abstract: In 2006, an outbreak of Chikungunya virus (CHIKV) of the Asian genotype affected over 200 people in Bagan Panchor village in Malaysia. One year later, a post-outbreak survey was performed to determine attack rate, asymptomatic rate, and post-infection sequelae. Findings were compared with recent CHIKV outbreaks of the Central/East African genotype. A total of 180 residents were interviewed for acute symptoms and post-infection physical quality of life and depressive symptoms. Sera from 72 residents were tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
48
2
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 13 publications
(15 reference statements)
4
48
2
3
Order By: Relevance
“…Studies also showed that seroprevalence was greater in the part of the village with more human activity. Besides, differences in attack rates were likely caused by local factors, including population immunity and genetic susceptibility, vector competence, environmental settings and effectiveness of outbreak control measures (Ayu et al 2010). In Mayotte, CHIKV seroprevalence was higher in households with structural risk factors for mosquito breeding or exposure, such as open yards (Raude & Setbon 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Studies also showed that seroprevalence was greater in the part of the village with more human activity. Besides, differences in attack rates were likely caused by local factors, including population immunity and genetic susceptibility, vector competence, environmental settings and effectiveness of outbreak control measures (Ayu et al 2010). In Mayotte, CHIKV seroprevalence was higher in households with structural risk factors for mosquito breeding or exposure, such as open yards (Raude & Setbon 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, IFN-α appears early in infection and correlates with viral load (111,114,117). Coincident with rising viral loads and IFN-α responses, the vast majority of infected patients experience sudden onset of clinical illness (Table 1), with a small proportion of infected individuals (5%-28%) remaining asymptomatic (118,119). Acute CHIKV infection is predominated by high fever (39°C-40°C), which can last up N-terminus of E3 traffics the major and minor structural polyproteins through the host secretory pathway, where cleavage by host proteases produces pE2 (E3-E2); 6K or transframe (TF); and E1.…”
Section: Disease Mechanisms and Host Immune Responsesmentioning
confidence: 99%
“…Studies of prior outbreaks have determined that 10%–70% of persons in an affected area become infected [1, 2]. This potentially high infection rate is coupled with a high symptomatic attack rate among infected people, with 50%–97% developing clinical disease with fever and polyarthralgia [24], and yields large outbreaks of disease that often tax existing healthcare systems and public health infrastructure.…”
mentioning
confidence: 99%
“…These findings suggest that the CHIKV was broadly transmitted during the outbreak. A total of 3%–22% of infected patients are asymptomatic or pauci-symptomatic [2, 4]. …”
mentioning
confidence: 99%